Nanoseismic monitoring for detection of rockfalls: experiments in quarry areas - Hskes, Carole; Fiorucci, Matteo; Iannucci, Roberto; Martino, Salvatore; Paciello, Antonella (Italian journal of engineering geology and environment, 2018)
<span data-sheets-value=""1":2,"2":"In the frame of early warning and risk mitigation studies for landslide processes involving rock masses, two quarry areas (Cala Rossa Bay in Sicily and Acuto in Central Italy) were monitored with SNS (Seismic Navigation System) arrays. In this study, 73 rockfalls were simulated by launches of rock blocks. This allowed to perform a back analysis for defining the best seismic velocity model of the subsoil half-space; the records related to each impact caused by the rock block launch were managed by the nanoseismic monitoring approach, varying the velocity model to obtain a theoretical epicentre as close as possible to the actual location of the impact point. In order to evaluate the sensibility of the SNS array, the results obtained by different array apertures and positions were compared in terms of azimuth and distance error with respect to the real epicentres. On the other hand, several natural rockfalls were detected; their analysis allowed to identify areas having higher susceptibility to rockfalls by using the previously calibrated subsoil half-space model. Further studies are required to better define the areas prone to rockfall generation in the considered test sites; nevertheless, the here obtained results show an encouraging perspective about the application of the nanoseismic monitoring with respect to vulnerable infrastructures in rockfall prone areas."" data-sheets-userformat=""2":15233,"3":"1":0,"10":1,"11":3,"12":0,"14":"1":2,"2":0,"15":"Arial","16":8">In the frame of early warning and risk mitigation studies for landslide processes involving rock masses, two quarry areas (Cala Rossa Bay in Sicily and Acuto in Central Italy) were monitored with SNS (Seismic Navigation System) arrays. In this study, 73 rockfalls were simulated by launches of rock blocks. This allowed to perform a back analysis for defining the best seismic velocity model of the subsoil half-space; the records related to each impact caused by the rock block launch were managed by the nanoseismic monitoring approach, varying the velocity model to obtain a theoretical epicentre as close as possible to the actual location of the impact point. In order to evaluate the sensibility of the SNS array, the results obtained by different array apertures and positions were compared in terms of azimuth and distance error with respect to the real epicentres. On the other hand, several natural rockfalls were detected; their analysis allowed to identify areas having higher susceptibility to rockfalls by using the previously calibrated subsoil half-space model. Further studies are required to better define the areas prone to rockfall generation in the considered test sites; nevertheless, the here obtained results show an encouraging perspective about the application of the nanoseismic monitoring with respect to vulnerable infrastructures in rockfall prone areas.